Partisipasi Wali Santri dalam Mendukung Program Pondok di Pondok Pesantren Darul Husaini NWDI Sanggeng Desa Kelebuh: Participation of Students' Guardians in Supporting the Boarding School Program at the Darul Husaini NWDI Sanggeng Islamic Boarding School, Kelebuh Village - Abd Quddus al Badani; Sirajun Nasihin; Bq Riskika Dewi (Pendidikan Al-Gafari, 2025)
Islamic boarding schools (pesantren) are among the oldest educational institutions in Indonesia, playing a central role in shaping the morals and spirituality of their students. As educational institutions that integrate religious knowledge with daily life, Islamic boarding schools have served as strongholds for preserving Islamic scholarly traditions and as agents of social change. This study aims to explore the forms of parental (wali santri) participation in supporting the programs of Pondok Pesantren Darul Husaini NWDI Sanggeng, and the extent to wich the participation of students’ guardians contributes to its succes and development. A qualitative approach was used, with data collected through interviews, observation, and documentation. The findings indicate that wali santri participate in three main forms: intellectual contribution, material support, and direct involvement in pesantren activities. They actively provide input on institutional policies, contribute financially to programs, and engage in religious and community events organized by the pesantren. Factors that encourage participation include trust in the pesantren, awareness of the importance of religious education, and effective communication between the pesantren and the parents. Meanwhile, barriers include time constraints, financial limitations, and lack of information about ongoing programs. The study concludes that active parental involvement is a key factor in the success of educational and character-building programs at the pesantren.